2019
DOI: 10.1136/bmjopen-2018-027134
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sustained hypertension and obesity among urban and rural adolescents: a school-based, cross-sectional study in North India

Abstract: ObjectiveRecent data on sustained hypertension and obesity among school-going children and adolescents in India are limited. This study evaluates the prevalence of sustained hypertension and obesity and their risk factors among urban and rural adolescents in northern India.SettingA school-based, cross-sectional survey was conducted in the urban and rural areas of Ludhiana, Punjab, India using standardised measurement tools.ParticipantsA total of 1959 participants aged 11–17 years (urban: 849; rural: 1110) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
(42 reference statements)
2
21
7
2
Order By: Relevance
“…BP also demonstrated interesting patterns across subgroups. SBP z-score was highest in the adolescents, which may be a reflection of a higher BMI z-score based on the known association between higher BMI and SBP [ 33 , 34 , 35 ]. In contrast, DBP z-score was highest in the preschool-age children.…”
Section: Discussionmentioning
confidence: 99%
“…BP also demonstrated interesting patterns across subgroups. SBP z-score was highest in the adolescents, which may be a reflection of a higher BMI z-score based on the known association between higher BMI and SBP [ 33 , 34 , 35 ]. In contrast, DBP z-score was highest in the preschool-age children.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies to date have evaluated the relationship between tooth decay and obesity; however, results are sometimes contradictory [6-9]. Although some studies have reported that the prevalence of obesity in India is high, its relationship with dental caries appears to be scant [10, 11]. Hence, this study assessed the correlation between age-specific body mass index (BMI) and dental caries in children aged three to 12 years.…”
Section: Introductionmentioning
confidence: 99%
“…28 The Million Death Study reported that about 75% of all road injury-related deaths were pedestrians and other vulnerable road users. 29 Our findings that ischaemic heart disease is in the top 10 causes of death for adolescents is surprising and disturbing, but not inconsistent with studies from India which have shown that cardiovascular risk factors such as obesity, 30 diabetes and hypertension 31 are increasing amongst adolescents 32 and that adolescents lack knowledge about cardiovascular disease (CVD) risk factors. 33 Results from NFHS-3 indicate that in the late adolescent age group, 29% of boys and 4% of girls had used tobacco.…”
Section: Discussionmentioning
confidence: 60%